Risk Aversion and its Impact on Medical Practice in Pakistan - Nadir Mehmood, Nadir Mehmood; Nadir Mehmood, M. Irfan Malik; M. Irfan Malik, M. Irfan Malik (Journal of Rawalpindi Medical College, 2018)
It has been a standard practice historically to categorize difficult patients and their therapeutic options based on initially subjective criteria and then a more objective one. In an effort to assess surgical decision-making and the outcome of surgery by different surgeons, surgeon specific outcome data was introduced to the US and UK surgery in 1991 and 2005 respectively, initially in cardiothoracic surgery. This data was made available to public access to named surgeon procedural outcome. It was associated with an improvement in patient outcome, but with a concern about changes in surgeon behaviour, upgrading of patients’ risk factor and cessation of low volume and/or poorly performing surgeons.